Association between the maximal distance of atrial septal protrusion and cryptogenic stroke. Issue 9 (December 2017) - Tokunaga, Keisuke; Yasaka, Masahiro; Kuwashiro, Takahiro; Gotoh, Seiji; Nakamura, Asako; Takaguchi, Go; Ago, Tetsuro; Kamouchi, Masahiro; Kitazono, Takanari; Okada, Yasushi
Background and purpose: Previous studies have suggested that atrial septal aneurysm is a potential risk factor for cerebral embolism. However, the association between the level of atrial septal protrusion and cerebral embolism is still unclear. The purpose of the present study was to assess the association between the maximal distance of atrial septal protrusion and cryptogenic stroke. Methods: A total of 588 consecutive acute ischemic stroke patients (70 ± 11 (mean ± SD) years, 401 men) who underwent transesophageal echocardiography were enrolled. The maximal distance of atrial septal protrusion into the right or left atrium was measured. Atrial septal aneurysm was diagnosed when the maximal distance of atrial septal protrusion was >10 mm. Cryptogenic stroke was defined as non-lacunar ischemic stroke without >50% proximal artery stenosis or occlusion, cardioembolic sources, ≥4 mm atherosclerotic plaques in the aortic arch, or carotid or vertebral artery dissection. Results: The rate of cryptogenic stroke increased with the increasing maximal distance of atrial septal protrusion. The maximal distance of atrial septal protrusion (multivariate-adjusted odds ratio (OR) per 1 mm, 1.14; 95% confidence interval (CI), 1.04–1.24; P = 0.003) and atrial septal aneurysm (multivariate-adjusted OR, 4.32; 95% CI, 1.22–20.39; P = 0.022) was independently associated with cryptogenic stroke. Conclusions: The maximal distance of atrial septal protrusion was independently associated with cryptogenic stroke.